Amino-functionalized poly(N-vinylcaprolactam) derived from lysine: a sustainable polymer with thermo and pH dual stimuli response. Issue 46 (8th November 2016) - Jia, Fan; Wang, Shixue; Zhang, Xiaojie; Xiao, Chunsheng; Tao, Youhua; Wang, Xianhong
Abstract : Lysine, a renewable feedstock with economic feasibility, was tactfully cyclized to its corresponding cyclic lysine and then subjected to a reaction with acetylenes to yield a sustainable N -vinylcaprolactam (VCL) derivative. Well-defined PVCL with pendent amino groups was prepared via MADIX/RAFT polymerization. Abstract : Lysine, a renewable feedstock with economic feasibility, was tactfully cyclized to its corresponding cyclic lysine and then subjected to a reaction with acetylenes to yield a sustainable N -vinylcaprolactam (VCL) derivative. Subsequent MADIX/RAFT copolymerization of the resultant monomer gave well-defined PVCL bearing pendant 2, 5-dimethylpyrrole protected amino groups with narrow polydispersity. 1 H NMR, SEC and MALDI-TOF-MS evaluations of the polymers demonstrated the controlled feature of the polymerization. Cleavage of the 2, 5-dimethylpyrrole protecting group produced amino-functionalized PVCL showing pH regulated thermo responsiveness. The lower critical solution temperature (LCST) can be regulated from 34 to 64 °C, by varying pH values, salt concentrations, and the molar percentage of amino groups. Moreover, these amino-functionalized PVCL exhibited cell compatibility. Thus, we have demonstrated a sustainable approach to regulate pH- and thermal-sensitivity of PVCL, while retaining most structural and chemical identity of PVCL.